Who benefits in a crisis? Evidence from hedge fund stock and option holdings - Aragon, George O.; Martin, J. Spencer; Shi, Zhen (Journal of Financial Economics, 2019)
We use a unique data set of hedge fund long equity and equity option positions to investigate a significant lockup-related premium earned during the tech bubble (1999–2001) and financial crisis (2007–2009). Net fund flows are significantly greater among lockup funds during crisis and noncrisis periods. Managers of hedge funds with locked-up capital trade opportunistically against flow-motivated trades of non-lockup managers, consistent with a hypothesis of rent extraction in providing crisis era liquidity. The success of this opportunistic trading is concentrated during periods of high borrowing costs, in less liquid stock markets, and is enhanced by hedging in the equity option market.